2017
DOI: 10.3198/jpr2017.04.0023crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of Oilseed Sunflower Germplasms RHA 461, RHA 462, RHA 463, HA 465, HA 466, HA 467, and RHA 468 with Diversity in Sclerotinia Resistance, Yield, and Other Traits

Abstract: Sclerotinia head and stalk rots are among the most devastating diseases in sunflower (Helianthus annuus L.). Breeding for resistance to these diseases while maintaining or improving yield and quality is complicated by the quantitative inheritance of the resistance, for which there are few genes of major effect. The objective of this work was to provide new diversity to sunflower breeding organizations for yield and Sclerotinia resistance, together with other useful agronomic and end user traits. Four restorer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…‘RHA 426’ (PI 617099) and ‘RHA 428’ are restorer inbred germplasms developed by the USDA‐ARS and the North Dakota Agricultural Experiment Station (NDAES) possessing imidazolinone herbicide tolerance and DM resistance conditioned by the Pl 34 gene, respectively (Miller and Al‐Khatib, 2002; Miller et al, 2002; Talukder et al, 2019). ‘RHA 463’ (PI 655014) is a restorer oilseed germplasm developed by the USDA‐ARS and the NDAES in 2006 (Hulke et al, 2018). ‘HA 466’ (PI 667183) is a Sclerotinia‐resistant, high‐oleic oilseed maintainer line released by the USDA and the NDAES in 2006 (Hulke et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…‘RHA 426’ (PI 617099) and ‘RHA 428’ are restorer inbred germplasms developed by the USDA‐ARS and the North Dakota Agricultural Experiment Station (NDAES) possessing imidazolinone herbicide tolerance and DM resistance conditioned by the Pl 34 gene, respectively (Miller and Al‐Khatib, 2002; Miller et al, 2002; Talukder et al, 2019). ‘RHA 463’ (PI 655014) is a restorer oilseed germplasm developed by the USDA‐ARS and the NDAES in 2006 (Hulke et al, 2018). ‘HA 466’ (PI 667183) is a Sclerotinia‐resistant, high‐oleic oilseed maintainer line released by the USDA and the NDAES in 2006 (Hulke et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…‘RHA 463’ (PI 655014) is a restorer oilseed germplasm developed by the USDA‐ARS and the NDAES in 2006 (Hulke et al, 2018). ‘HA 466’ (PI 667183) is a Sclerotinia‐resistant, high‐oleic oilseed maintainer line released by the USDA and the NDAES in 2006 (Hulke et al, 2018). ‘Almanzor’ was a hybrid evaluated in the Food and Agriculture Organization (FAO) Hybrid Sunflower Yield Trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RHA 418 (PI 607508) and RHA 419 (PI 619204) are oilseed restorer lines released by the USDA and NDAES in 1998 and 1999, respectively (Miller et al, 2002). RHA 468 (PI 667184) is an imidazolinone herbicide tolerant oilseed restorer line released by the USDA and NDAES in 2006 (Hulke et al, 2017). Both RHA 419 and RHA 468 carry the Pl ARG gene for downy mildew resistance.…”
Section: Methodsmentioning
confidence: 99%
“…RHA 477 is a downy mildew–resistant, imidazolinone herbicide–tolerant F 6 –derived F 9 restorer oilseed sunflower line selected from the cross RHA 468/R‐7009. Downy mildew resistance is conferred by the Pl ARG gene, which provides resistance to all known races of downy mildew (Hulke et al, 2017; Qi et al, 2017). For each F 8 plant that made up the breeder seed of RHA 477, a greenhouse test showed that 20 seedlings exhibited resistance to downy mildew, with zero susceptible, indicating that each head row was fixed for resistance with 99% confidence based on Sedcole's test.…”
Section: Characteristicsmentioning
confidence: 99%